(untitled) (Journal of Surgical Sciences, 2020)
We report a rare case of c-kit negative gastrointestinal stromal tumor with metastasis in left cervical lymph nodes and subcutaneous tissue. The patient presented to us with recurrent neck swelling, perforation of gas containing hollow viscous and multiple subcutaneous swellings. After confirmation of diagnosis we transferred the patient to medical oncologist. Patient expired two months after starting chemotherapy. Journal of Surgical Sciences (2017) Vol. 21 (2): 115-117